2001
DOI: 10.1034/j.1600-9657.2001.170107.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enamel matrix derivative (EMDOGAIN®) upon periodontal healing after replantation of permanent incisors in Beagle dogs

Abstract: This study histologically assessed the effect of enamel matrix derivative (EMDOGAIN) on periodontal healing in re-implanted teeth in nine Beagle dogs. Incisors in dogs were re-implanted after 15, 30 and 60 min of dry storage with and without the application of EMDOGAIN. The pulps were removed in all teeth. In groups 1 and 2, dog teeth were splinted and the dogs sacrificed after 8 and 12 weeks, respectively. In group 3, dog teeth were not splinted and sacrifice took place after 12 weeks. The histological parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 16 publications
4
101
0
2
Order By: Relevance
“…In contrast, only a few investigations on the precise mechanisms have been reported with regard to the relationship between tooth implantation or replantation and regeneration of the periodontal ligament (Iqbal and Bamaas, 2001;Kawanami, et al, 2001;Lekic et al, 2001;Lin et al, 2000).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast, only a few investigations on the precise mechanisms have been reported with regard to the relationship between tooth implantation or replantation and regeneration of the periodontal ligament (Iqbal and Bamaas, 2001;Kawanami, et al, 2001;Lekic et al, 2001;Lin et al, 2000).…”
Section: Introductionmentioning
confidence: 84%
“…EMDOGAIN may also create an environment conducive to the formation of acellular cementum when applied to a mechanically exposed or an acid etched surface of dentin . Another study in beagle dogs has reported that the effect of EMDOGAIN upon periodontal healing is more pronounced at a 12-week interval after the replantation of permanent incisors (Iqbal and Bamaas, 2001).…”
Section: Enamel Matrix Derivative (Emdogain)mentioning
confidence: 99%
“…Among these mediators, enamel matrix protein (EMD) has proven to be efficacious in periodontal regeneration [3][4][5]. Recently, the use of EMD has been suggested in pulpotomies [6,7] and the management of avulsed permanent teeth due to its effects on the healing process [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…11 Fluoride acts on the bone tissues, cementum and dentin, by converting hydroxyapatite into fluorapatite which is more resistant to resorption. Of late Iqbal and Bamaas 12 showed that extracted dogs' teeth air-dried for periods up to 60 minutes benefited from surface treatment with an enamel matrix derivative gel before replantation. Periodontal healing was greater for the treated teeth than for control teeth, and there was less replacement resorption.…”
Section: Discussionmentioning
confidence: 99%